MISKONSEPSI MAHASISWA PADA MATA KULIAH STATISTIKA DESKRIPTIF MATERI UKURAN TENDENSI SENTRAL, UKURAN DISPERSI, DAN UKURAN LETAK - Sutrisno Sutrisno; Yanuar Hery Murtianto (Universitas PGRI Semarang, 2016)
The purpose of this research is to identify student misconceptions in the subject Descriptive Statistics on material of Measures of Central Tendency, Measures of Dispersion, and Measures of Placemark and its cause. This descriptive qualitative research using the technique of written tests, interviews, and documentation in collecting data.The focus of this research is student misconceptions.The subjects were students of the second semester math education group F University PGRI Semarang 2015/2016 academic year were selected by purposive sampling.Test the credibility of the data in this research use triangulation techniques.The results showed that every student has a different misconceptions appropriate to academic ability.In outline, student misconceptions is the determination of the use of parameters and statistics according to the origin of the data provided.This misconception will impact on the next misconception is elections in notation and use of formulas that were not appropriate.This is because the learning difficulties of students in the form of the prerequisites material are not yet well understood, less complete understanding of the definition of a concept, has not been able to develop auxiliary table as needed calculations, as well as lack carefully situations in workmanship matter.Keywords: Misconceptions, Descriptive Statistics, Measures in Statistics